Paediatric non-progression following grandmother-to-child HIV transmission. Issue 1 (December 2016) - Tsai, M.-H.; Muenchhoff, M.; Adland, E.; Carlqvist, A.; Roider, J.; Cole, D.; Sewell, A.; Carlson, J.; Ndung'u, T.; Goulder, P.
Abstract Background In contrast to adult HIV infection, where slow disease progression is strongly linked to immune control of HIV mediated by protective HLA class I molecules such as HLA-B*81:01, the mechanisms by which a minority of HIV-infected children maintain normal-for-age CD4 counts and remain clinically healthy appear to be HLA class I-independent and are largely unknown. To better understand these mechanisms, we here studied a HIV-infected South African female, who remained a non-progressor throughout childhood. Results Phylogenetic analysis of viral sequences in the HIV-infected family members, together with the history of grand-maternal breast-feeding, indicated that, unusually, the non-progressor child had been infected via grandmother-to-child transmission. Although HLA-B*81:01 was expressed by both grandmother and grand-daughter, autologous virus in each subject encoded an escape mutation L188F within the immunodominant HLA-B*81:01-restricted Gag-specific epitope TL9 (TPQDLNTML, Gag 180–188). Since the transmitted virus can influence paediatric and adult HIV disease progression, we investigated the impact of the L188F mutant on replicative capacity. When this variant was introduced into three distinct HIV clones in vitro, viral replicative capacity was abrogated altogether. However, a virus constructed using thegag sequence of the non-progressor child replicated as efficiently as wildtype virus. Conclusion These findings suggest alternative sequences of events: the transmission of the uncompensated low fitness L188F to both children, potentially contributing to slow progression in both, consistent with previous studies indicating that disease progression in children can be influenced by the replicative capacity of the transmitted virus; or the transmission of fully compensated virus, and slow progression here principally the result of HLA-independent host-specific factors, yet to be defined.